Pedestrian route choice by elementary school students: the role of street network configuration and pedestrian quality attributes in walking to school. Issue 2 (2nd April 2016) - Ozbil, Ayse; Argin, Gorsev; Yesiltepe, Demet
Abstract: This study examines the extent to which street network configuration is associated with path selection by pedestrians. The aim is to better understand how the spatial layout of the street network affects pedestrian route choice behavior, controlling for pedestrian quality attributes. Randomly selected 6th, 7th, and 8th grade students (ages 12–14) from 15 elementary schools in Istanbul, Turkey were asked to draw their routes walking between home and school. Preliminary findings suggest that when all areas are merged into a single set, global choice, which measures the degree to which a street segment is located in between the shortest paths connecting all pairs of origins and destinations, and metric reach, which measures the street length that is accessible within a walking range, are significantly associated with route selection jointly with the distance to school, sidewalk width, distribution of pedestrians as well as the number of non-residential land-uses. However, directional reach, which measures the extent to which streets are sinuous or aligned, appears to be a strong correlate of route selection in the analysis of individual areas. From a design policy point of view, designing better connected street networks with reduced directional distance between home and school might serve as supporting navigation choices and walking behavior.